Configuring and Installing Computer Application of Bestlink College of the Philippines for Senior High School Computer Laboratory: Vol.3, No.1D (Ascendens Asia Singapore – Bestlink College of the Philippines Journal of Multidisciplinary Research, 2024)
The research project Configuring and Installing Computer Application of the Bestlink College of the Philippines for Senior High School Computer Laboratory. In this study, the researcher performs activities on the computer to learn how to configure and install computer applications in the BCP Computer laboratory. The researchers conclude that the importance of application configuration and application installation. The researcher interviewed ICT teachers about configuring and installing computer applications to gather qualitative data. The researchers also observed that. In this study, to learn more about computer application configuration and installation, the researcher goes to Bestlink College of the Philippines Computer   Laboratory to interview the ICT teachers. We prepare a set of questions that the respondent can answer, and those answers will be used to know the situations and gather some information that will be very helpful through this study.